Draft Annual Plan 1981-82 North Eastern Council - Planning Commission (Planning Commission, 1981)
The current year's Annual Plan of the North Eastern Council was originally fixed at Rs. 60 crores but was later enhanced to Rs. 64.4 crores, the additional amount ”as earmarked for Roads ( Rs. 2 crores), transmission lines (Rs. 2 crores) and a mini cement plant (Rs. 40 lakhs). Though the NEC's development programmes were expected to cost Rs. 64.4 crores during the year, North Eastern Electric Power Corporation Ltd.(NEEPCO), the implementing agency for the Kopili Hydro Electric Project for the NEC, was asked to raise some resource by way of loan from lending institutions.
North Eastern Council
North Eastern Council